THE CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND THEIR READING COMPREHENSION OF THE EIGHT GRADE STUDENTS OF SMP NEGERI 3 BAUBAU - Jafar, Rifandi (Jurnal Akademik FKIP Unidayan, 2023)
The Formulation of the problem in this study was whether there was a Correlation between Students‟ Vocabulary Mastery and Their Reading Comprehension of the eight grade students of SMP Negeri 3 Baubau. This study aimed to determine The Correlation between Students‟ Vocabulary Mastery and Their Reading Comprehension of the eight grade students of SMP Negeri 3 Baubau. Data Collection in this study was carried out using research instruments in the form of multiple choices tests. This study used a quantitative approach using the correlation method. The data obtained were analyzed by descriptive analysis and inferential analysis. The Result of this study indicated the correlation Value (R) of 0.942 Where the Value was included in the Strong category. In addition, the value of Fcount was 430.981 and Ftable 4.10, so that Fcount was greater than Ftable (430.981>4.10), and the significance value was 0.000 where the value was less than α 0.05. Based on these results, it could be concluded that Ha was accepted and H0 was rejected. This meant that there was a positive correlation and there was a significant influence between Students’ Vocabulary Mastery and Their Reading Comprehension of the eight grade students of SMP Negeri 3 Baubau.